New Long-Term Use Solid Bismuth Microelectrode Arrays for Rapid and Sensitive Determination of Sunset Yellow in Isotonic Beverages and Water Samples by Adsorptive Stripping Voltammetry - Mieczyslaw Korolczuk; Iwona Gęca; Artur Mazurek; Paulina Mrózek (Molecules)
This article reports on the long-term use, solid bismuth microelectrode arrays for the first time. The presented working microelectrode is characterized by particular advantages compared to bismuth film electrodes and solid single bismuth microelectrodes; these advantages include environmentally friendly properties and the amplification of recorded currents, which are subsequently more resistant to interference. The proposed solid bismuth microelectrode array was applied to develop an adsorptive stripping voltammetric procedure for Sunset Yellow determination. The main experimental parameters were optimized. The calibration graph was linear from 5 × 10−9 to 1 × 10−7 mol L−1 (time of accumulation, 60 s). The detection limit was equal to 1.7 × 10−9 mol L−1. The relative standard deviation for a concentration of Sunset Yellow of 2 × 10−8 mol L−1 was 4.1% (n = 7). Potential interference effects were examined. The presented analytical procedure was applied for the determination of Sunset Yellow in isotonic beverages and the results were confirmed by HPLC as a comparative method. The correctness of the presented procedure was also confirmed by satisfactory recovery values obtained during the analysis of spiked environmental water samples.